Genomic abundance and transcriptional activity of diverse gypsy and copia long terminal repeat retrotransposons in three wild sunflower species - Qiu, Fan; Ungerer, Mark C. (My University, 2018)
Background: Long terminal repeat (LTR) retrotransposons are highly abundant in plant genomes and require transcriptional activity for their proliferative mode of replication. These sequences exist in plant genomes as diverse sublineages within the main element superfamilies (i.e., gypsy and copia). While transcriptional activity of these elements is increasingly recognized as a regular attribute of plant transcriptomes, it is currently unknown the extent to which different sublineages of these elements are transcriptionally active both within and across species. In the current report, we utilize next generation sequencing methods to examine genomic copy number abundance of diverse LTR retrotransposon sublineages and their corresponding levels of transcriptional activity in three diploid wild sunflower species, Helianthus agrestis, H. carnosus and H. porteri. Results: The diploid sunflower species under investigation differ in genome size 2.75-fold, with 2C values of 22.93 for H. agrestis, 12.31 for H. carnosus and 8.33 for H. porteri. The same diverse gypsy and copia sublineages of LTR retrotransposons were identified across species, but with gypsy sequences consistently more abundant than copia and with global gypsy sequence abundance positively correlated with nuclear genome size. Transcriptional activity was detected for multiple copia and gypsy sequences, with significantly higher activity levels detected for copia versus gypsy. Interestingly, of 11 elements identified as transcriptionally active, 5 exhibited detectable expression in all three species and 3 exhibited detectable expression in two species. Conclusions: Combined analyses of LTR retrotransposon genomic abundance and transcriptional activity across three sunflower species provides novel insights into genome size evolution and transposable element dynamics in this group. Despite considerable variation in nuclear genome size among species, relatively conserved patterns of LTR retrotransposon transcriptional activity were observed, with a highly overlapping set of copia and gypsy sequences observed to be transcriptionally active across species. A higher proportion of copia versus gypsy elements were found to be transcriptionally active and these sequences also were expressed at higher levels.
Citation: Qiu, F., & Ungerer, M. C. (2018). Genomic abundance and transcriptional activity of diverse gypsy and copia long terminal repeat retrotransposons in three wild sunflower species. BMC Plant Biology, 18(1). https://doi.org/10.1186/s12870-017-1223-z
Keywords: Retrotransposons; Gypsy; Copia; Genomic abundance; Transcriptional activity; Sunflower